2020
DOI: 10.21272/jnep.12(3).03007
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured ZnO and CuI Thin Films on Poly(Ethylene Terephthalate) Tapes for UV-Shielding Applications

Abstract: In this work, we study a suitability for protection against terrestrial ultraviolet part of the solar spectrum of undoped and doped by indium zinc oxide thin nanostructured films, ZnO and ZnO:In, respectively, and cuprous iodide (CuI) films obtained via Successive Ionic Layer Adsorption and Reaction (SILAR) techniques on the lightweight low cost poly(ethylene terephthalate) (PET) flexible substrates. The film morphology is observed by scanning electron microscopy (SEM). Chemical compositions of the films are i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 18 publications
0
5
0
1
Order By: Relevance
“…It is important that XRF spectra of CuI/PI and CuI/PET samples contain quite a lot of sulfur atoms. The presence of sulfur is a distinctive feature of CuI films obtained by the SILAR method [9,10], since the solution of the cationic precursor contains a chemically unstable thiosulfate ion. According to [4,5], the acceptor impurity S can replace iodine and iodine vacancies and thereby increase the conductivity of CuI.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is important that XRF spectra of CuI/PI and CuI/PET samples contain quite a lot of sulfur atoms. The presence of sulfur is a distinctive feature of CuI films obtained by the SILAR method [9,10], since the solution of the cationic precursor contains a chemically unstable thiosulfate ion. According to [4,5], the acceptor impurity S can replace iodine and iodine vacancies and thereby increase the conductivity of CuI.…”
Section: Resultsmentioning
confidence: 99%
“…The advantage of chemical solution deposition is the easy introduction of foreign atoms, which is convenient and efficient for doping [5]. In our earlier works [9,10], we found that CuI films obtained by the SILAR method on various substrates are enriched in copper, but contain sulfur and possible oxygen, which enter them from aqueous precursor solutions. The aim of this work is to study the morphology, chemical composition, crystal structure, and charge transport in nanostructured conducting thermoelectric copper(I) iodide films obtained by the SILAR method to create flexible thermoelectric materials.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The results indicated that the UV-protection capacity of CuI films on NC substrates falls within the "excellent" category, with sun protection factors reaching up to 9211 for the finest CuI film produced via the SILAR method. Additionally, nanostructured ZnO and CuI thin films on poly(ethylene terephthalate) tapes demonstrated effective UV-shielding applications [72].…”
Section: Successive Ionic Layer Adsorption and Reaction (Silar) Techn...mentioning
confidence: 99%
“…Оксид цинку -це прямозонний напівпровідник з шириною забороненої зони близько 3,37 еВ та енергією зв'язку екситону 60 меВ). Він є перспективним для використання як матеріял для виготовлення прозорих контактів і деяких інших важливих застосувань [1][2][3], фотоприймачів [4], світлодіод [5]. Зокрема, в [2] було встановлено придатність наноструктурованих тонких плівок оксиду Цинку для захисту від земної ультрафіолетової частини сонячного спектру, одержаних хемічним методом на недорогих гнучких підкладинках, а у праці [3] наведено результати дослідження наночастинок оксиду Цинку, активованих гамма випроміненням, які показали, що в структурі ZnO відсутні істотні зміни, і вони можуть бути використані для лікування раку.…”
Section: вступunclassified